2015
DOI: 10.1021/acs.cgd.5b01076
|View full text |Cite
|
Sign up to set email alerts
|

Local and Extended-Order Evolution of Synthetic Talc during Hydrothermal Synthesis: Extended X-ray Absorption Fine Structure, X-ray Diffraction, and Fourier Transform Infrared Spectroscopy Studies

Abstract: Synthetic talc is a new filler of industrial interest due to its submicron size, its chemical and mineral purity, and its hydrophilic character. To develop this filler on a preindustrial scale, this work aimed to understand the mechanisms of transformation from the amorphous talc precursor to crystalline synthetic talc. X-ray diffraction, Fourier transform infrared spectroscopy, and extended X-ray absorption fine structure at Ni–K edge techniques were used to study a Ni-talc series composed of a talc precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…studied the talc precursor (from P3) aged with time and temperature by XRD, FTIR and NMR spectroscopy and showed that talc precursor evolves structurally with time in the ( ab ) plane while the stacking order in the c * direction is limited (Figure ). Contrary to Lèbre who described talc precursor as a brucite sheet and few polymerized silicon tetrahedra, an extended X‐ray absorption fine structure (EXAFS) study showed that Ni‐talc precursor was a nanotalc entity; the talc growth unit was constituted by 2–3 Ni‐octahedra distanced from each other by 3.07 Å and 3–4 Si‐tetrahedra distributed on the top and bottom of the octahedral “sheet” and distanced from Ni by 3.29 Å …”
Section: Amorphous And/or Short‐range Order Nanotalcmentioning
confidence: 70%
See 1 more Smart Citation
“…studied the talc precursor (from P3) aged with time and temperature by XRD, FTIR and NMR spectroscopy and showed that talc precursor evolves structurally with time in the ( ab ) plane while the stacking order in the c * direction is limited (Figure ). Contrary to Lèbre who described talc precursor as a brucite sheet and few polymerized silicon tetrahedra, an extended X‐ray absorption fine structure (EXAFS) study showed that Ni‐talc precursor was a nanotalc entity; the talc growth unit was constituted by 2–3 Ni‐octahedra distanced from each other by 3.07 Å and 3–4 Si‐tetrahedra distributed on the top and bottom of the octahedral “sheet” and distanced from Ni by 3.29 Å …”
Section: Amorphous And/or Short‐range Order Nanotalcmentioning
confidence: 70%
“…Contrary to Lbre [57] who described talcp recursor as ab rucite sheet and few polymerized silicon tetrahedra, an extended X-ray absorption fine structure (EXAFS) study showedt hat Ni-talc precursor wasananotalc entity;t he talc growth unit was constituted by 2-3 Ni-octahedra distanced from each other by 3.07 and 3-4 Si-tetrahedra distributed on the top and bottom of the octahedral "sheet" and distanced from Ni by 3.29 . [128] Simultaneously to the research of magnesium silicate precipitation for developing new materials, basic research on magnesium silicate was conducted in cement research. Magnesium silicateh ydrateg el having an Mg/Sir atio of 0.75 was precipitated and characterized by NMR spectroscopy,X RD, FTIR and SEM.…”
Section: Formed At the Beginning Of Precipitationmentioning
confidence: 99%
“…Dumas et al. explained that the synthetic talc precursor entities (formed at the mixer point, upstream the reactor) are already formed of 10 Å‐wide T‐O‐T arrangements . So, due to its numerous hydroxyl groups, the synthetic talc precursor can easily form hydrogen bonds and polar interaction with water.…”
Section: Ultra‐fast Continuous Synthesis Of Minerals In Scwmentioning
confidence: 99%
“…This phenomenonc an be explained by combinede ffects.D umas et al explained that the synthetic talc precursor entities( formed at the mixer point, upstream the reactor) are already formed of 10 -wide T-O-T arrangements. [50] So, due to its numeroush ydroxyl groups, the synthetic talc precursor can easily form hydrogen bonds and polar interaction with water.I ns upercritical conditions, the drastic fall of the water density andd ielectric constantr estricts the solvation of particles and consequently favors the convergence andi nterlocking of synthetic talc precursors. Consequently,t he supercritical domain favors the growth of particles of synthetic talc.…”
Section: The Scw Continuouss Ynthesis Of Talcmentioning
confidence: 99%
“…[6,7] Micron-sized synthetic talc particles can be easily obtained after few months of hydrothermal synthesis in batch reactor. [8,9] Thep ossibility to finely tune particle-size and to obtain nano-sized particles was the beginning of synthetic talc material research. [8,9] Thep ossibility to finely tune particle-size and to obtain nano-sized particles was the beginning of synthetic talc material research.…”
mentioning
confidence: 99%